Performance of cuprous oxide mesoparticles with different morphologies as catalysts in a carbon nanotube ink for printing electrochemical sensors - Veiga, Lionel S. (2020)
A simplified, surfactant-free method is presented for the synthesis of cuprous oxide mesoparticles involving the use of only three reactants at room temperature. Different morphologies, such as cubes, cuboctahedra, truncated octahedra, octahedra, hexapods, and porous spheres could be obtained using different concentrations of reactants. The roles played by each reactant in the synthesis are critically discussed. The mesoparticles were used in the formulation of carbon nanotube-based waterborne inks to prepare coated electrodes. The electrocatalytic activity of the different cuprous oxide mesoparticles used in the inks towards hydrogen peroxide reduction was measured and compared. Cuprous oxide hexapods yielded the highest sensitivity whereas porous spheres were superior in terms of stability. The combination of carbon nanotubes and cuprous oxide mesoparticles in waterborne ink allows printing of electrodes combining electrical conduction and electrocatalysis in a single layer printed onto flexible substrates.